Computational creativity without computers - Roncoroni, Umberto (2024)
Computational creativity and generative artificial-intelligence algorithms pose new challenges to artists and educators. This study investigates the main aesthetic, educational, and methodological contradictions of these technologies, including the influence of Romantic aesthetics, the lack of a proper relationship between digital and traditional culture, and the limits of quantitative approaches to creativity. Based on a literature review, an experimental software design, and artistic practices, demonstrates that digital technology alone is insufficient in developing the essential skills needed for computational creativity in artistic production and education. Inclusive, sustainable, and creative uses of digital media require the development of aesthetically updated proprietary technology rooted in the cultural identities of its origin. Our conclusions highlight the technological role of the humanities and the importance of ethnocomputation artifacts, such as the yupana, and analog processes and materials in the meta-medium and metacreativity domains. © 2024, Universidade Catolica Portuguesa. All rights reserved.